438PEvaluating mitochondrial biomarkers between fatigue subclasses identified using latent class analysis in early-stage breast cancer patients. (24th November 2019) - Toh, Y L; Maung, S; Chan, A
Abstract: Background: Given that CRF is characterized by a lack of energy, it is postulated that mitochondrial dysfunction may contribute to its etiology. Using mitochondrial DNA (mtDNA) copy number and displacement-loop (D-loop) mutation status, this study aims to evaluate mtDNA content between fatigue subclasses, over the course of chemotherapy. Methods: In a prospective cohort study, early-stage breast patients' fatigue levels were assessed using the validated Multi-Dimensional Fatigue Symptom Inventory–Short Form (MFSI-SF) and their blood was drawn before, during and after treatment. Relative mtDNA copy number was determined via real-time quantitative polymerase chain reaction while mitochondrial genome was sequenced directly for D-loop mutations at nucleotide positions 303, 489 and 514. Subclasses of extent of fatigue was derived using latent class analysis, based on magnitude of change in sub-domain scores after treatment, with respect to baseline. Clinically relevant factors that differentiate the identified subclasses were then compared between the fatigued groups. Results: A total of 133 patients (mean age ± SD: 51.2 ± 8.8 years, median mtDNA: 71.0) were classified into two fatigue subclasses: mild fatigue (75.2%) and fatigued group (24.8%) respectively. Based on mtDNA trajectory, patients who are predisposed to CRF started off with lower baseline values and experienced slower recovery. Median mtDNA content was reduced over 12 weeks after initiation of chemotherapy (p < 0.001) and was reported to be consistently lower in fatigued group (T2: 48.0 vs 56.0; T3: 61.4 vs 66.0) although the difference was not found to be statistically significant. The proportion of patients with D-loop mutation status was comparable between fatigued group and mild fatigue (303: 81.8% vs 73.0%, 489: 45.5% vs 47.0% and 514: 45.5% vs 53.0%). However, no association was reported between mtDNA levels over time or D-loop mutation with CRF status. Conclusions: mtDNA content and D-loop mutation status do not sufficiently differentiate fatigue subclasses, suggesting that future research may be needed to study the differential expression of mitochondrial dysfunction-related genes and the pathways they may perturb. Legal entity responsible for the study: National University of Singapore. Funding: National Medical Research Council. Disclosure: All authors have declared no conflicts of interest.